Design of chemically modified bacteriorhodopsin films for information protection systems - Trikur, Ivan; Batori-Tartsi, Zita; Sichka, Mykhailo; Rizak, Galina; Rizak, Vasyl (Eastern-European Journal of Enterprise Technologies, 2022)
The object of this study is the processes of interaction of fragments of purple membranes with certain chemicals, which affect the photochromic properties of bacteriorhodopsin films. This paper considers the possibility of modifying the properties of bacteriorhodopsin films by changing their chemical composition, which will make it possible to use such films to protect information. For this purpose, it has been determined which optical properties of bacteriorhodopsin are most important for its use in the field of information protection; films were made using various chemicals as impurities. It was shown that the introduction of impurities does not affect the absorption spectrum of bacteriorhodopsin, which indicates that it retains its properties. It has been established that impurity substances are evenly distributed in films. By studying the dynamics of photoinduced changes in films with different concentrations of chemical components, the effect of chemical modification on the photocycle of bacteriorhodopsin and the properties of film structures based on it was studied. Based on the results of experimental studies, it was found that by changing the chemical composition of films, it is possible to change the time of storage of the information recorded on them in the range from several to hundreds of seconds continuously. The sensitometric sensitivity of film structures also depends on the chemical composition and can vary in the range from 3.9·10–3 to 54·10–3 m2/J. At the same time, chemical modification is simpler from a technological point and cheaper from a financial point of view compared to other methods that make it possible to achieve similar results. The reported results suggest that chemically modified films based on bacteriorhodopsin have great potential for practical application in the field of information protection and access control